Using music in teaching Finnish as a second language - Miletic, Aleksandra (2018)
The thesis describes a case study research carried out at the Language Centre at the University of Jyväskylä. The aim of the study was to discover the extent to which music is being used, as a teaching tool, among Finnish teachers who teach Finnish as an L2 for adults. This study also aims to explore how teachers use music as a teaching tool, and how their beliefs impact their teaching practices. Semi-structured interviews were conducted with four teachers. The interviews with the teachers were recorded and they were analyzed using qualitative content analysis to answer the research questions. The research found that all study participants, to a certain extent, either use or have used music as a teaching tool in their classrooms. According to the teachers, they use music in several ways for different language teaching purposes. All teachers believe that music can have a positive impact on learners’ memory and that it can be a motivation tool for learners. Keywords: L2 teaching, L2 learning, music, teaching tool, learning tool, teachers’ beliefs, case study.